1998
DOI: 10.1001/jama.280.15.1321
|View full text |Cite
|
Sign up to set email alerts
|

The Origin, Content, and Workload of E-mail Consultations

Abstract: Context.-Despite the common use of e-mail, little beyond anecdote or impressions has been published on patient-clinician e-mail consultation. Objective.-To report our experiences with free-of-charge e-mail consultations. Design.-Retrospective review of all e-mail consultation requests

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
1
2

Year Published

1998
1998
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(95 citation statements)
references
References 13 publications
3
89
1
2
Order By: Relevance
“…Most of the diseases or problems were uncommon. These findings are consistent with previous studies, 3,13 including 2 evaluating the overall usage of a digital health sciences library 14 and the e-mail the digital library receives. 2 In contrast, the most common medical problems in the e-mails were quite different from the most common problems seen in a general pediatrician's office 15 or in a pediatric telephone triage line, 16,17 which are primary care problems.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Most of the diseases or problems were uncommon. These findings are consistent with previous studies, 3,13 including 2 evaluating the overall usage of a digital health sciences library 14 and the e-mail the digital library receives. 2 In contrast, the most common medical problems in the e-mails were quite different from the most common problems seen in a general pediatrician's office 15 or in a pediatric telephone triage line, 16,17 which are primary care problems.…”
Section: Discussionsupporting
confidence: 92%
“…One third of these e-mails were pediatric-related. 2 Another study of solicited pediatric email consultations from unknown patients found that most information requests come from patients and family members who sent detailed patient-specific information 3 that was also consistent with a study of unsolicited e-mails sent to the authors of a tutorial on the temperomandibular joint. 4 Another recent report studied how physicians and Web masters (persons who run Internet sites) handled unsolicited e-mails and found a wide variation in practice.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…E-mail communication, with patients or between clinicians, raises concerns about patient confidentiality and profes- sional liability and generally lacks mechanisms for physician reimbursement. 33,34 Given that nearly three-quarters of U.S. adults currently report e-mail or internet access, 35 the low rate of physician-patient e-mail communication suggests a lack of appropriate clinical infrastructure rather than lack of patient access. 36,37 Low use may also reflect negative attitudes, resistance, and/or inertia among physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Today, due to the fast growing and penetration of the INTERNET and mobile telephone technology, the IT applications in the health care environment are focused at e-consultation [2] and home care delivery [3] and the use of triage systems [4]. Home care delivery is becoming a very important issue, especially for the management of chronic diseases such as diabetes, congestive heart failure, coronary heart disease, etc.…”
Section: Introductionmentioning
confidence: 99%